1977
DOI: 10.1073/pnas.74.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of native human hemoglobin from separated globin chains and alloplex intermediates.

Abstract: A complete experimental format is given for the reconstitution of human hemoglobin from the separated heme-free a-and -globin chains (a', ft') and hemin, by two alternative routes. Based on their oxygen binding properties, the reaction of the ferri-forms with reducing agent, and the response of the oxygen binding curves to pH variation and to the addition of the a losteric effector 2,3-diphosphoglycerate, the molecules are native. One reconstitution route uses direct addition of hemin to the separated globin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 13 publications
3
72
0
Order By: Relevance
“…Analysis by CD spectropolarimetry revealed that the resulting apo-␣-globin retains considerable, but much reduced, ␣-helical structure (ϳ30% ␣-helix) in the absence of the heme group. This result is in agreement with previous studies of apo-hemoglobin and its subunits, which demonstrated that removal of heme causes a greater destabilization of ␣-globin secondary structure than of ␤-globin (24,25). A UV-visible wavelength absorption spectrum indicated that contamination of the apo-␣-globin preparation with heme-containing protein was at levels below 1% (ratio of absorption, A 420 /A 280 ϭ 0.04 (26)).…”
Section: Ahsp and The Ahsp⅐␣-globin Complex Are Predominantlysupporting
confidence: 83%
See 1 more Smart Citation
“…Analysis by CD spectropolarimetry revealed that the resulting apo-␣-globin retains considerable, but much reduced, ␣-helical structure (ϳ30% ␣-helix) in the absence of the heme group. This result is in agreement with previous studies of apo-hemoglobin and its subunits, which demonstrated that removal of heme causes a greater destabilization of ␣-globin secondary structure than of ␤-globin (24,25). A UV-visible wavelength absorption spectrum indicated that contamination of the apo-␣-globin preparation with heme-containing protein was at levels below 1% (ratio of absorption, A 420 /A 280 ϭ 0.04 (26)).…”
Section: Ahsp and The Ahsp⅐␣-globin Complex Are Predominantlysupporting
confidence: 83%
“…In the absence of AHSP, apo-␣-globin cannot be detected by gel filtration chromatography; it appears to interact with the chromatography system in such a way that no discrete protein peak is observed. Notably, apo-␣-globin has previously been shown to form high sedimentation coefficient aggregates resulting in exclusion from gel filtration systems (24). In addition, higher yields of soluble apo-␣-globin were obtained when lyophilized protein was taken up in buffer already containing AHSP.…”
Section: Ahsp and The Ahsp⅐␣-globin Complex Are Predominantlymentioning
confidence: 82%
“…As noted above, however, likely the exact sequence of events during Hb folding and assembly in vitro can be modulated by external conditions such as solvent, pH, presence of chaperones, etc. [45]. …”
Section: Hemoglobin Refolding Monitored By Esi-msmentioning
confidence: 99%
“…is still a matter of debate [28,[42][43][44], and apparently there is more than one viable assembly pathway leading from the isolated subunits to native Hb [45].…”
mentioning
confidence: 99%
See 1 more Smart Citation